Taxes and portfolio composition - Elton, Edwin J.; Gruber, Martin J. (Journal of Financial Economics, 1978)
This paper explores investors portfolio behavior when security returns can be described by one of the forms of the CAPM model and investors pay taxes. The conditions under which an investor holds the market portfolio are explored. In addition the extent to which securities are held in proportions which differ from market weights are shown to be functions of tax rates, dividend policies, and the variance covariance structure between all securities.